Parameter Optimisation of Aerobic Granular Sludge at High Temperature Using Response Surface Methodology - Syahira Ibrahim; Norhaliza Abdul Wahab; Aznah Nor Anuar; Mustafa Bob (Institute of Advanced Engineering and Science, 2017)
This paper proposes an improved optimisation of sequencing batch reactors (SBR) for aerobic granular sludge (AGS) at high temperature-low humidity for domestic wastewater treatment using response surface methodology (RSM). The main advantages of RSM are less number of experiment required and suitable for complex process. The sludge from a conventional activated sludge wastewater treatment plant and three sequencing batch reactors (SBRs) were fed with synthetic wastewater. The experiment were carried out at different high temperatures (30, 40 and 50°C) and the formation of AGS for simultaneous organics and nutrients removal were examined in 60 days. RSM is used to model and to optimize the biological parameters for chemical oxygen demand (COD) and total phosphorus removal in SBR system. The simulation results showed that at temperature of 45.33°C give the optimum condition for the total removal of COD and phosphorus, which correspond to performance index R2 of 0.955 and 0.91, respectively.